RETROSPECTIVE DOSE RECONSTRUCTION WITH MOBILE PHONES AND CHIP CARDS - Ekendahl, Daniela; Čemusová, Zina; Judas, Libor (Radiation protection dosimetry, 2019)
Mobile phones and common chip cards are very widespread items that almost everyone owns. They contain some radiation-sensitive materials that can be used for dosimetry based on stimulated luminescence. We investigated and compared reproducibility, dose response and fading of luminescence signal for the particular materials. Subsequently, we performed an experiment of a dose reconstruction using mobile phones and chip cards, which were fixed to a slab phantom and irradiated by a 137Cs radiation source in our laboratory. Doses obtained were compared with reference values. The materials investigated can be used for dosimetry in cases of serious radiation accidents or malevolent acts with radioactive materials, when it is extremely important to identify as quickly as possible individuals who received high-radiation doses.
Keywords: Equipment Design; luminiscence; teplota; Radiometry; fantomy radiodiagnostické; Reproducibility of Results; Calibration; termoluminiscenční dozimetrie; radiometrie; mobilní telefon; Cesium Radioisotopes; Temperature; kalibrace; reprodukovatelnost výsledků; Cell Phone; únik radioaktivních látek; Phantoms, Imaging; Radioactive Hazard Release; radioizotopy cesia; Luminescence; Radiation Dosage; design vybavení; dávka záření; vztah dávky záření a odpovědi; Thermoluminescent Dosimetry; Dose-Response Relationship, Radiation